Disseminating improved practices: Are volunteer farmer trainers effective? - Lukuyu, Ben A.; Place, Frank; Franzel, Steven; Kiptot, E. (Informa UK Limited, 2012)
Purpose: This paper assesses the effectiveness of volunteer farmer trainers in promoting adoption of agricultural technologies in western Kenya. Specifically, the purpose was to assess the type of information they disseminated, farmer trainers' characteristics desirable to farmer trainees, and how trainees evaluate farmer trainers. Design/methodology/approach: Data were collected through focused group and open discussions, and interviews with 44 farmer trainers (32% women) and 91 trainees (63% women). Effectiveness of training was assessed based on level of learner satisfaction and attributes pertaining to knowledge, skill, attitude and application of the learning on farms. Other topics examined included selection of farmer trainers, organization of training, type, how and to whom information is disseminated, and farmer trainers' constraints and opportunities. Findings: Farmer trainers played important roles such as mobilizing and training fellow farmers, hosting demonstration plots, bulking and distributing planting materials. They were, however, rated slightly lower in follow-ups and seed bulking. Farmer trainers disseminate on average two to four different types of technology. Crop-based technologies were disseminated more than livestock-based ones because of their simplicity. Technical backstopping from extension workers remains a challenge, which may compromise quality of information disseminated. The survey showed that the approach is sustainable, with farmer trainers continuing their work several years after project support had ended. Practical implications: The results from this study are of use to development programmes keen on using low-cost, community-based dissemination approaches. Recommendations are also given on selecting farmer trainers, organizing training, types of technologies to disseminate incentives, and sustainability. Originality/value: The added value lies in filling information gaps in the use and effectiveness of the farmer trainer approach in promoting technology dissemination.